Prospects for the institute of administrative responsibility in the Republic of Kazakhstan - G. R. Rakhmetova; M. O. Altaeva; G. Serik (Хабаршы. Заң сериясы, 2022)
Administrative liability is one of the types of legal liability arising from the commission of violations that do not pose a danger. In Soviet and post-Soviet times, the institute of administrative responsibility received its scientific justification and stable normative consolidation. The works of well-known administrative scientists, such as Bakhrakh D.N., Alekseev S.S., Kozlov Yu.M., Lazarev Yu.M., are devoted to this institute, among Kazakh scientists it is necessary to single out Abrakhmanov B., Zhatkanbayeva A.E., Zhetpisbayeva B.A., Podoprigora R.A., and a number of others. At the same time, it is the institute of administrative responsibility that has undergone significant adjustments in the scientific field that has lost interest. What is the reason for this? What are the prospects for this type of responsibility in the normative and practical directions? What to expect from the legislator in the near future? Historically, administrative responsibility is one of the most common types of responsibility. Administrative enforcement measures are an important instrument of state regulation of the activities of individuals and legal entities, and in relation to legal entities, in fact, the only and, accordingly, the most important. Accordingly, due to the amendments made to the Code of Administrative Offences, we consider it necessary to analyze the current state and prospects for the development of the institute of administrative responsibility in the Republic of Kazakhstan.